2021
DOI: 10.17221/166/2020-pps
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic bioagent mechanisms of controlling potato soft rot

Abstract: Bacterial antagonists are effective as an alternative to synthetic bactericides in the control of potato soft rot. The use of bioagents reduces the application of synthetic bactericides, which are harmful to humans and the environment. However, the mechanisms of some bioagents, such as some fungi and bacteria, are not yet understood. This paper reviews the current situation of potato soft rot, biological controls, antagonistic bioagents and their mechanisms, application strategies and future directions in toda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 96 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…The above results indicate that improving the assimilation and utilization efficiency of nitrate can promote the growth of plants and indirectly enhance plant disease resistance [ 86 , 87 ]. In addition, the defensive systems of plants could be enhanced by the bioagents, by increasing the antioxidant genes, which would eventually increase plant growth and yield production [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above results indicate that improving the assimilation and utilization efficiency of nitrate can promote the growth of plants and indirectly enhance plant disease resistance [ 86 , 87 ]. In addition, the defensive systems of plants could be enhanced by the bioagents, by increasing the antioxidant genes, which would eventually increase plant growth and yield production [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potato is another crop that largely benefits from the utilisation of biocontrol agents to prevent tuber soft rotting caused by Pectobacterium spp., Dickeya spp., and Clostridium spp. [160]. The overall strategy includes soaking potato tubers prior to sowing in a solution containing Pseudomonas fluorescens strains to prevent future colonisation by pathogens.…”
Section: Biocontrol Agentsmentioning
confidence: 99%
“…Finally, cocktails of biocontrol agents in the form of a solution or powder are used to protect harvested tubers during storage. In this case, the tubers are soaked in the solution prior to storage [160]. A significant reduction in economic losses caused by rice blast incited by Magnaporthe oryzae is expected to be obtained through the application of Streptomyces strains as biocontrol agents [161,162].…”
Section: Biocontrol Agentsmentioning
confidence: 99%
“…has expanded significantly (Helepciuc & Todor, 2022). Numerous studies have shown the great potential of B. amyloliquefaciens in suppressing R. solanacearum, as well as bacteria from the genus Pectobacterium (Chen et al, 2019;Osei et al, 2021). In this study, two B. amyloliquefaciens strains, , with previously proven antagonistic potential against several pathogens, were examined for antimicrobial activity against pathogenic bacteria isolated from the potato in Serbia using in vitro, in situ, and in planta tests to find effective and environmentally friendly control agents against destructive potato diseases.…”
Section: Introductionmentioning
confidence: 99%